A corpus of regional Dutch speech - Nerbonne, John; Ommen, Sandrien van; Gooskens, Charlotte; Impe, Leen; Kürschner, Sebastian (Phonetics in Europe. Perception and production, 2013)
We present in this paper a phonetically transcribed corpus of regional Dutch speech from the Netherlands and Belgian Flanders and some example analyses using it. The corpus consists not only of 200 common words, but also of 200 nonsense words as these were pronounced by radio announcers from regional radio stations. The announcers regularly speak on radio programs with an explicitly regional remit, and they agreed to our recording them using regional speech but also using the standard language (standard Netherlandic Dutch in the Netherlands and standard Belgian Dutch in Flanders), which they also spoke professionally. The corpus is publicly available for analyses concerning, e.g., the relative differences between Dutch and Belgian regional speech, the relative similarity of regional speech to standard speech in the two countries, and the probity of models such as Auer’s & Hinskens’ (1996) “cone model”, within which regional speech should be found. Nerbonne, Van Ommen, Wieling & Gooskens (to appear) have indeed used the corpus material to test whether regional speech adheres to the predictions of the cone model.
Keywords: Dutch; Belgian; standard language

Alte und neue Sprachminderheiten – alte und neue Forschungsperspektiven - Kürschner, Sebastian (Sprachminderheiten: gestern, heute, morgen - Minoranze linguistiche: ieri, oggi, domani., 2014)
The paper discusses research perspectives applied to language minorities, including the connection between language and culture, language policy and planning, the "birth" and "death" of minority languages, as well as grammatical and lexical peculiarities of minority languages. It furthermore addresses the advantages that speakers of minority languages may have from their multilingualism.
Keywords: Sprachminderheiten; Germanistische Linguistik; Romanistik

(angenommen) Dialects of German, Dutch and the Scandinavian languages - Kürschner, Sebastian (Handbook of dialectology, 2015)
Keywords: dialect; German; Dutch; Scandinavia; dialectology

Collitz, Hermann (1855-1935) - Kürschner, Sebastian (2006)
UnivIS-Import:2015-04-20:Pub.2006.phil.dgeko.LGDSM.collit
Keywords: Lexikon; Biograpie; Hermann Collitz

Complexity in nominal plural allomorphy. A contrastive survey of ten Germanic languages - Dammel, Antje; Kürschner, Sebastian (Language complexity: Typology, contact, change., 2008)
We investigate the complexity of nominal plural allomorphy in ten Germanic languages from a contrastive and diachronic perspective. Focusing on one language family allows us to develop multidimensional criteria to measure morphological complexity and to compare different diachronical drifts. We introduce a three-step complexity metric, involving (1) a quantitative step, (2) a qualitative step, and (3) a validation step comparing the results from step (1) and (2) to actual language use. In this article, we apply the method’s two first steps to the plural allomorphy of our sample languages. Our criteria include for (1) the number of allomorphs and for (2) iconicity in form-meaning relationship, the basis of allomorph assignment, and the direction of determination between stem and suffix. Our approach reveals Faroese as the most complex language and English as the simplest one.
UnivIS-Import:2015-04-16:Pub.2008.phil.dgeko.LGDSM.comple
Keywords: Germanic languages; morphology; Faroese; English

Computing and language variation - Nerbonne, John; Gooskens, Charlotte; Kürschner, Sebastian; van Bezooijen, Renée (Edinburgh University Press, 2009)
Keywords: computing; language variation

Cross-border intelligibility - on the intelligibility of Low German among speakers of Danish and Dutch - Gooskens, Charlotte; Kürschner, Sebastian (Low Saxon dialects across borders - Niedersächsische Dialekte über Grenzen hinweg, 2009)
Abstract (Deutsch) Entlang der deutsch-dänischen und deutsch-niederländischen Staatsgrenzen haben sich Bruchstellen im niederdeutschen Dialektkontinuum herausgebildet. Im vorliegenden Beitrag untersuchen wir, wie sich die Entstehung solcher Bruchstellen auf die Verstehbarkeit der dialektalen Varietäten über die Grenze hinweg auswirkt. Auf Grundlage der Ergebnisse eines Experiments wird zu diesem Zweck das Hör-verständnis niederdeutscher Wörter bei dänischen und niederländischen Testpersonen aus grenznahen und grenzfernen Gebieten verglichen. Es stellt sich heraus, dass die grenznahen Testpersonen in den Nordost-Niederlanden das Niederdeutsche signifikant besser verstehen als die grenzfernen Testpersonen. In Dänemark hingegen ist der Unterschied zwischen den grenznahen und grenzfernen Testpersonen nicht signifikant. Weiterhin zeigt sich, dass die niederländischen Testpersonen mehr niederdeutsche Wörter verstehen als die dänischen. Auf Grundlage einer Analyse auf der Wortebene kann gezeigt werden, dass die grenznahen Testpersonen in den Niederlanden vor allem solche niederdeutschen Wörter besser verstehen, die den dialektalen Varietäten des Grenzgebiets ähnlicher sind als ihren standardniederländischen Entsprechungen. Bei den dänischen Testpersonen ist das hingegen nicht der Fall. Das dialektale Kontinuum an der deutsch-niederländischen Grenze scheint somit noch erhalten zu sein, während es an der deutsch-dänischen Grenze bereits stark geschwächt ist. Abstract (English) The Low German dialect continuum has been disturbed by national borders to the north along the Danish-German border, and to the west along the Dutch-German border. In combination with strong standardization processes in both countries this has resulted in growing distance between the dialects spoken on both sides of these borders. In this article, we describe research conducted into the linguistic consequences of the two state borders, not only on the structure of the varieties themselves, but also on the mutual intelligibility across the borders. In the Netherlands, the intelligibility scores of subjects from the border area were significantly higher than those of non-border subjects. In Denmark, however, the difference in intelligibility scores between the border group and the non-border group was not significant. Furthermore, the results show that Dutch subjects understand more Low German words than Danish sub-jects do. An analysis of the results on the level of the word shows that Dutch sub-jects often score better when confronted with Low German words resembling dialectal North-Eastern Dutch words more than their Standard Dutch counterparts. Similar results were not found for Danish subjects. Our results indicate that the continual relationship between North-Eastern Dutch and Low German is still existent, while it is much weaker in the German-Danish situation.
Keywords: Low German; Dutch; Danish; dialectology; intelligibility

Cross-border intelligibility. On the intelligibility of Low German among speakers of Danish and Dutch - Kürschner, Sebastian; et al. (Low Saxon dialects across borders - Niedersächsische Dialekte über Grenzen hinweg, 2009)
UnivIS-Import:2015-10-26:Pub.2009.phil.dgeko.LGDSM.crossb

Deens is makkelijker voor Friezen dan voor Nederlanders - feit of fabel? [Dänisch ist für Friesen leichter als für Niederländer - wahr oder falsch?] [Danish is easier for Frisian-speaking than for Dutch-speaking people - fact or fiction?] - van Bezooijen, Renée; Gooskens, Charlotte; Kürschner, Sebastian (Philologia Friscia, 2012)
UnivIS-Import:2015-04-20:Pub.2012.phil.dgeko.LGDSM.deensi
Keywords: Verstehbarkeit; Dänisch; Friesisch; Niederländisch

Deklinationsklassen-Wandel: Eine diachron-kontrastive Studie zur Entwicklung der Pluralallomorphie im Deutschen, Niederländischen, Schwedischen und Dänischen - Kürschner, Sebastian (Walter de Gruyter, 2008)
UnivIS-Import:2015-04-02:Pub.2008.phil.dgeko.vvasp.deklin
Keywords: Morphologie; Deklinationsklasse; Sprachgeschichte; Allomorphie

De Nederlandse meervoudsallomorfie tussen Duitse complexiteit en Engelse eenvoud [Die niederländische Pluralallomorphie zwischen deutscher Komplexität und englischer Simplizität] [Dutch plural allomorphy between German complexity and English simplicity] - Kürschner, Sebastian (Nederlands tussen Duits en Engels. Handelingen van de workshop op 30 september en 1 oktober 2005 aan de Freie Universität Berlin, 2006)
The comparison of the plural formation of the three Germanic languages Dutch, German, and English reveals different degrees of complexity. While English only uses the s-plural (with three variants) productively, Dutch and German are characterized by competing productive plural allomorphs: Dutch uses the s- and the (e)n-plural, and German has even more allomorphs, which include not only suffixes, but also stem allomorphy (umlaut). In this article, basic assumptions on morphological complexity are made and tested with respect to the plural allomorphy employed in these three languages. Complexity is based on multidimensional factors, namely 1) the number of forms and formal processes employed, 2) allomorph conditioning, 3) intra-systematic variation, and 4) formal redundancy versus zero realization of the relevant plural concept. The results confirm Van Haeringen’s (1956) assumption that Dutch can be positioned between German and English (‘Nederlands tussen Duits en Engels’), with Dutch having a special status with respect to intra-systematic variation.
UnivIS-Import:2015-04-20:Pub.2006.phil.dgeko.LGDSM.denede
Keywords: Deutsch; Englisch; Pluralallomorphie; Niederländisch

Die Interaktion von Deklinationsklasse und Genus in oberdeutschen Dialekten - Kürschner, Sebastian (Formen und Funktionen: Morphosemantik und grammatische Konstruktion, 2016)
Keywords: Deklination; Deklinationsklasse; Genus; Oberdeutsch; Morphologie; Dialektologie

Et databasemøde mellem Jensen og Müller. Om kontrastiv antroponomastisk metodik [Ein Datenbanktreffen zwischen Jensen und Müller: Zur kontrastiven anthroponomastischen Methodologie] [On contrastive anthroponomastic methodology] - Farø, Ken; Kürschner, Sebastian (Tijdschrift voor Skandinavistiek, 2007)
UnivIS-Import:2015-03-09:Pub.2007.phil.dgeko.LGDSM.etdata

Familiennamen als Basis der Spitznamenbildung. Ein deutsch-schwedischer Vergleich - Kürschner, Sebastian (Linguistik der Familiennamen, 2014)
In both German and Swedish, the formation of nicknames is often based on a person’s legal name. The paper compares nicknames derived from family names such as German Mülli < Müller and Swedish Dalle < Dahlqvist. A corpus of such nicknames and corresponding family names is assembled from player profiles found on the websites of amateur sports teams. It is shown that both languages prefer bisyllabic, trochaic nicknames, mostly resulting from shortening and suffixation. Expressive marking is achieved by the use of the i-suffix in German and by expressive geminates in Swedish. Although many family names are transparent with respect to other lexical units, most of the nicknames are opaque. Interestingly, the use of family names as a basis of nicknames is most often found with men in German, while Swedish shows a more balanced picture between the sexes.
Keywords: Deutsch; Schwedisch; Namenforschung

Flexionsklassenwandel im Vergleich. Nominale und verbale Entwicklungen in vier germanischen Sprachen - Kürschner, Sebastian; Dammel, Antje (Sprachwandelvergleich - Comparing diachronies, 2013)
Keywords: Flexionsklasse; Nominalflexion; Verbflexion; Dänisch; Schwedisch; Deutsch; Niederländisch

Fuge-n-kitt, voeg-en-mes, fuge-masseund fog-e-ord - Fugenelemente im Deutschen, Niederländischen, Schwedischen und Dänischen. Ein Grenzfall der Morphologie im Sprachkontrast - Kürschner, Sebastian (Kontrastive Germanistische Linguistik, 2010)
This article compares linking elements occurring in nominal compounds in German, Dutch, Swedish and Danish. The linking systems differ most strikingly with respect to syllabic elements, which are primarily distributed with respect to declension classes and gender in German and Swedish, semantics in Danish, and declension class and plural meaning in Dutch. Regarding functionalization, there are tendencies to mark nouns with animate reference in Danish (and secondarily also in German and Swedish) and to build trochaic structures in word languages. The most consistent parallel between the languages is found in the linking-s be-coming a perceptual marker which functions to signal the end of morphologically (and, in German, phonologically) complex modifiers.
Keywords: German; Dutch; Swedish; Danish; linking elements

Fuge-n-kitt, voeg-en-mes, fuge-masse und fog-e-ord - Fugenelemente im Deutschen, Niederländischen, Schwedischen und Dänischen: ein Grenzfall der Morphologie im Sprachkontrast. (Linking elements in German, Dutch, Swedish, and Danish contrast). - Kürschner, Sebastian (Kontrastive Germanistische Linguistik, 2010)
UnivIS-Import:2015-10-26:Pub.2010.phil.dgeko.LGDSM.fugenk
Keywords: Morphologie; Fugenelemente

Grenzgänger zwischen Flexion und Wortbildung. Zur Geschichte des dänischen Fugen-s [On the history of Danish linking-s] - Kürschner, Sebastian (Über Grenzen. Grenzgänge der Skandinavistik. Festschrift zum 65 Geburtstag von Heinrich Anz, 2007)
UnivIS-Import:2015-04-20:Pub.2007.phil.dgeko.LGDSM.grenzg
Keywords: Flexion; Wortbildung; Dänisch; Fugen-s

...ham blev der dog Noget af, skjøndt hans Navn endte på "sen" - Om at hedde Andersen i den danske navneverden [Was es bedeutet, in der dänischen Namenwelt "Andersen" zu heißen] - Kürschner, Sebastian (2007)
UnivIS-Import:2015-03-09:Pub.2007.phil.dgeko.LGDSM.hamble
Keywords: Skandinavien; Namensforschung; Dänisch

Hans Christian Andersen zum 200. Geburtstag: "Mein Leben ist ein schönes Märchen, so reich und glücklich." - Blume, Svenja; Kürschner, Sebastian (Kovac, 2005)
UnivIS-Import:2015-05-08:Pub.2005.phil.dgeko.LGDSM.vonhan

Holtsmark, Anne (1896-1974) - Kürschner, Sebastian (2006)
UnivIS-Import:2015-04-20:Pub.2006.phil.dgeko.LGDSM.holtsm
Keywords: Lexikon; Anne Holtsmark

Horacek, Blanka (1913-2001) - Kürschner, Sebastian (2006)
UnivIS-Import:2015-04-20:Pub.2006.phil.dgeko.LGDSM.horace
Keywords: Lexikon; Blanka Horacek

Hvilken indflydelse har danske stød og svenske ordaccenter på den dansk-svenske forståelse? [Welchen Einfluss haben dänischer 'Stød' und schwedische Wortakzente auf die dänisch-schwedische Verstehbarkeit?] [How do Danish 'stød' and Swedish word accents influence Swedish-Danish intelligibility?] - Gooskens, Charlotte; Kürschner, Sebastian (Svenskans beskrivning 30. Förhandlingar vid Trettionde sammankomsten for svenskans beskrivning, Stockholm den 10 och 11 oktober 2008, 2010)
Keywords: Dänisch; Schwedisch; Wortakzent; Verstehbarkeitsforschung

Intelligibility of Standard German and Low German to speakers of Dutch - Gooskens, Charlotte; Kürschner, Sebastian; van Bezooijen, Renée (Dialectologia, 2011)
This paper reports on the intelligibility of spoken Low German and Standard German for speakers of Dutch. Two aspects are considered. First, the relative potential for intelligibility of the Low German variety of Bremen and the High German variety of Modern Standard German for speakers of Dutch is tested. Second, the question is raised whether Low German is understood more easily by subjects from the Dutch-German border area than subjects from other areas of the Netherlands. This is investigated empirically. The results show that in general Dutch people are better at understanding Standard German than the Low German variety, but that subjects from the border area are better at understanding Low German than subjects from other parts of the country. A larger amount of previous experience with the German standard variety than with Low German dialects could explain the first result, while proximity on the sound level could explain the second result.
Keywords: Intelligibility; German; Low German; Dutch; Levenshtein Distance; language contact

Intelligibility of Swedish for Danes: loan words compared with inherited words - Gooskens, Charlotte; Kürschner, Sebastian; van Bezooijen, Renée (Language for its own sake. Essays on language and literature offered to Harry Perridon, 2012)
Keywords: loan words; inherited words; Danish; Swedish

Interskandinavisk ordforståelse. En internetbaseret undersøgelsesmetode [Interskandinavisches Wortverstehen: Eine internetbasierte Untersuchungsmethode] [Inter-Scandinavian word intelligibility: An Internet-based research method] - Kürschner, Sebastian; Gooskens, Charlotte (Svenskans beskrivning 29. Förhandlingar vid Tjugonionde sammankomsten för svenskans beskrivning. Vasa den 4 och 5 maj 2007 (= Skrifter utgivna av Svenska-österbottniska samfundet 70), 2008)
UnivIS-Import:2015-04-16:Pub.2008.phil.dgeko.LGDSM.inters
Keywords: Verstehbarkeitsforschung

Kontrastive Germanistische Linguistik - Kürschner, Sebastian; et al. (Olms, 2010)
UnivIS-Import:2016-02-10:Pub.2010.phil.dgeko.LGDSM.kontra

Kontrastive germanistische Linguistik [Contrastive linguistics of the Germanic languages] - Dammel, Antje; Kürschner, Sebastian; Nübling, Damaris (Olms, 2010)
Keywords: Deutsch; Verbalflexion; Nominalflexion; Jiddisch; Luxemburgisch; Friesisch; Afrikaans; Färöisch; Isländisch; Wortbildung; Phonologie; Syntax; Textlinguistik; Lexikologie; Pragmatik

Kontrastive Linguistik. Überschaubar oder überblickslos? Entwicklung und Stand der bibliographischen Dokumentation in der kontrastiven Germanistik [On the development of bibliographic documentation in Contrastive Germanic Linguistics] - Kürschner, Sebastian (Philologia Fenno-Ugrica, 2007)
UnivIS-Import:2015-03-09:Pub.2007.phil.dgeko.LGDSM.kontra

Language variation studies and computational humanities. Introduction - Nerbonne, John; Gooskens, Charlotte; Kürschner, Sebastian; van Bezooijen, Renée (International Journal of Humanities and Arts Computing, 2009)
UnivIS-Import:2015-03-09:Pub.2009.phil.dgeko.LGDSM.langua
Keywords: language variation; computational linguistics; dialectology

"Lazarus" und "Lazi","Milo" und "Spatz", "Stinker" und "Stinkili". Bildung und Gebrauch "offizieller" und "inoffizieller" Katzennamen. - Ganslmayer, Christine; Kürschner, Sebastian (Tiernamen - Zoonyme. Band I: Haustiere., 2015)
Keywords: Katzennamen; Tiernamen; Zoonyme; Onomastik

Linguistic determinants of the intelligibility of Swedish words among Danes - Kürschner, Sebastian; Gooskens, Charlotte; van Bezooijen, Renée (International Journal of Humanities and Arts Computing, 2009)
In the present investigation we aim to determine to which degree various linguistic factors contribute to the intelligibility of Swedish words among Danes. We correlated the results of an experiment on word intelligibility with eleven linguistic factors and carried out logistic regression analyses. In the experiment, the intelligibility of 384 frequent Swedish words was tested among Danish listeners via the Internet. The choice of eleven linguistic factors was motivated by their contribution to intelligibility in earlier studies. The highest correlation was found in the negative correlation between word intelligibility and phonetic distances. Also word length, different syllable numbers, foreign sounds, neighbourhood density, word frequency, orthography, and the absence of the prosodic phenomenon of ‘stød’ in Swedish contribute significantly to intelligibility. Although the results thus show that linguistic factors contribute to the intelligibility of single words, the amount of explained variance was not very large (R2 (Cox and Snell) = .16, R2 (Nagelkerke) = .21) when compared with earlier studies which were based on aggregate intelligibility. Partly, the lower scores result from the logistic regression model used. It was necessary to use logistic regression in our study because the intelligibility scores were coded in a binary variable. Additionally, we attribute the lower correlation to the higher number of idiosyncrasies of single words compared with the aggregate intelligibility and linguistic distance used in earlier studies. Based on observations in the actual data from the intelligibility experiment, we suggest further steps to be taken to improve the predictability of word intelligibility.
UnivIS-Import:2015-03-09:Pub.2009.phil.dgeko.LGDSM.lingui
Keywords: Swedish; Danish; intelligibility

Linking elements in Germanic - Fuhrhop, Nanna; Kürschner, Sebastian (Word formation. An international handbook of the languages of Europe, 2014)
Linking elements such as -s in German Versicherung-s-vertreter, are found in between the parts of word-formation products in several Germanic languages. Systematic and functional aspects of linking elements are first introduced with respect to German. After that, a survey of other Germanic languages is provided. In parallel across the Germanic languages, the distribution of linking elements is different from that of the inflectional markers they stem from. Linking-s is distributed based on morphological (and, in German, prosodic) complexity, suggesting a function as morphological boundary marker across languages. The distribution of syllabic elements is more language-specific and based on semantic, rhythmic, and inflectional characteristics, respectively.
UnivIS-Import:2015-04-20:Pub.2014.phil.dgeko.LGDSM.imdruc_9
Keywords: Grammatik; Morphologie; Fugenelemente; Deutsch

Linking elements - origin, change and functionalization - Kürschner, Sebastian; Szczepaniak, Renata (Springer Netherlands, 2013)
UnivIS-Import:2015-04-02:Pub.2013.phil.dgeko.LGDSM.linkin
Keywords: grammar; Grammatik; morphology; Morphologie; linking elements: Fugenelemente; German; Deutsch

Linking elements - origin, contact, change. Introduction - Kürschner, Sebastian; Szczepaniak, Renata (Morphology, 2013)

Mål! - Gol! - Tor! - om fodboldsprog [Zur Fußballsprache] [On football language] - Farø, Ken; Kristensen, Kjeld; Kürschner, Sebastian (Mål og mæle, 2006)
UnivIS-Import:2015-03-09:Pub.2006.phil.dgeko.LGDSM.mlgolt

Methodik moderner Dialektforschung. Erhebung, Aufbereitung und Auswertung von Daten am Beispiel des Oberdeutschen. - Habermann, Mechthild; Kürschner, Sebastian; Müller, Peter O. (Olms, 2019)
Keywords: Dialektologie; Dialektologentagung; Oberdeutsch

Methodik moderner Dialektforschung. Erhebung, Aufbereitung und Auswertung von Daten am Beispiel des Oberdeutschen - Kürschner, Sebastian; Habermann, Mechthild; Müller, Peter O. (Olms, 2019)

Morphological non-blocking in Dutch plural allomorphy: a contrastive approach - Kürschner, Sebastian (Language typology and universals, 2009)
Dutch simplex nouns ending in schwa have two regular plural forms, e.g. bode-s/bode-n ‘messengers’. This means that neither of the two allomorphs -s and -n is blocked. Such regular non-blocking is non-existent in the closely related languages German and Afrikaans. To identify the reasons for this divergence, the history of plural marking in the three languages is compared. Based on the historical observations it is argued that the doublets in Dutch are retained due to the output principle of plurals ending in a trochaic foot, according to which both -s and -n may apply without preference on stems with non-final stress.
Keywords: nominal inflection; allomorphy; Dutch; Afrikaans; German; language change

På jagt efter en 'chokolade-forklaring' på den inter-skandinaviske kommunikation [Auf der Suche nach einer Erklärung der interskandinavischen Kommunikation] - Kürschner, Sebastian; Gooskens, Charlotte (2008)
UnivIS-Import:2015-03-09:Pub.2008.phil.dgeko.LGDSM.pjagte
Keywords: Skandinavien; interskandinavische Kommunikation

Paulston, Christina Bratt (b. 1932) - Kürschner, Sebastian (2006)
UnivIS-Import:2015-04-20:Pub.2006.phil.dgeko.LGDSM.paulst
Keywords: Lexikon; Christina Bratt Paulston

Pluralallomorphie in zehn germanischen Sprachen: Konvergenzen und Divergenzen in Ausdrucksverfahren und Konditionierung - Dammel, Antje; Kürschner, Sebastian; Nübling, Damaris (Kontrastive Germanistische Linguistik, 2010)
This article compares the noun plural systems of ten Germanic languages focusing on the number of allomorphs, their formal shape and the assignment principles used for allomorph distribution. It further aims at identifying the interrelating factors, categories, and features decisive for the very different ways in which plural allomorphy is organized in languages of the same origin. The major relevant factors are pointed out with special emphasis on the role of gender, semantic and rhythmic assignment, and the role of high token frequency. On formal grounds, the fusion vs. separation of case and number as well as the role of zero morphology vs. redundant marking, of stem alternation and the direction of influence between stem and affix are discussed.
Keywords: Pluralallomorphie; Germanische Sprachen

(Review) Fabian Fahlbusch/Rita Heuser/Jessica Nowak/Mirjam Schmuck (2012): Deutscher Familiennamenatlas. Band 3: Morphologie der Familiennamen. Berlin/New York: de Gruyter. 785 Seiten. - Kürschner, Sebastian (2013)
UnivIS-Import:2015-03-09:Pub.2013.phil.dgeko.LGDSM.review
Keywords: Rezension; Review; Familiennamen; names of families; Morphologie; morphology

(Rezension) Eckhard Meineke unter Mitarbeit von Judith Schwerdt (2001): Einführung in das Althochdeutsche (UTB für Wissenschaft 2167). Paderborn/München/Wien/Zürich: Schönigh. 350 Seiten, 15 Abbildungen, 23 Karten. - Kürschner, Sebastian (2012)
UnivIS-Import:2015-03-09:Pub.2012.phil.dgeko.LGDSM.rezens
Keywords: Rezension; Althochdeutsch

(Rezension) Irmgard Lindestam (2008): Norstedts stora tyska ordbok. Tysk-svensk. Svensk-tysk. Stockholm: Norstedts Akademiska Förlag und Steinarsson. 748 Seiten. Und Heimir Steinarsson (2008): þýsk-íslensk orðabók. Wörterbuch Deutsch-Isländisch. Reykjavík: Opna. 966 Seiten. - Kürschner, Sebastian (2012)
UnivIS-Import:2015-03-09:Pub.2012.phil.dgeko.LGDSM.rezens_6
Keywords: Rezension; Wörterbuch; Deutsch; Schwedisch; Isländisch

(Rezension) Janusz Stopyra (2008): Nominale Derivation im Deutschen und im Dänischen (Acta Universitatis Wratislaviensis 3051). Wroclaw: Uniw. Wroclawskiego. 245 Seiten. Zugleich: Habil.-Schrift 2009 (Germanica Wratislaviensia 128). Breslau: Univ. Breslau. 248 Seiten. - Kürschner, Sebastian (2010)
UnivIS-Import:2015-03-09:Pub.2010.phil.dgeko.LGDSM.rezens
Keywords: Rezension; Nomen; Wortbildung; Derivation; Deutsch; Dänisch

(Rezension) Ludger Zeevaert (2004): Interskandinavische Kommunikation. Strategien zur Etablierung von Verständigung zwischen Skandinaviern im Diskurs (Philologia 64). Hamburg: Dr. Kovac. 409 Seiten. - Kürschner, Sebastian (2007)
UnivIS-Import:2015-03-09:Pub.2007.phil.dgeko.LGDSM.ludger
Keywords: Rezension; Skandinavien; interskandinavische Kommunikation; Verständigung

(Rezension) Matthias Katerbow/Alexander Werth (2010) (Hrsg.): Moderne Regionalsprachen als multidimensionales Forschungsfeld (Germanistische Linguistik 210). Hildesheim/Zürich/New York: Olms. 208 Seiten. - Kürschner, Sebastian (2014)
Keywords: Rezension; Regionalsprachen

(Rezension) Roos Beerkens (2010): Receptive multilingualism as a language mode in the Dutsch-German border area (Zivilgesellschaftliche Verständigungsprozesse vom 19. Jahrhundert bis zur Gegenwart. Deutschland und die Niederlande im Vergleich 4). Münster u.a.: Waxmann. 330 Seiten. - Kürschner, Sebastian (2012)
UnivIS-Import:2015-03-09:Pub.2012.phil.dgeko.LGDSM.rezens_3
Keywords: Rezension; Multilingualismus; Dänisch-deutsche Grenze; Dänisch; Deutsch

(Rezension) Staffan Nyström/Eva Brylla/Katharina Leibring/Lennart Ryman/Per Vikstrand (2012) (Hrsg.): Binamn. Uppkomst, bildning, terminologi och bruk. Handlingar från NORNA:s 40:e symposium i Älkarleö, Uppland, 29/9-1/10 2010. With summaries in English (NORNA-rapporter 88). Uppsala: NORNA-förlaget. 198 Seiten. [Beinamen. Herkunft, Bildung, Terminologie und Gebrauch] - Kürschner, Sebastian (2014)
Keywords: Rezension; Namensforschung; Beiname

(Rezension) Ton Goeman/Marc van Oostendorp/Piet van Reenen/Oele Kornwinder/Boudewijn van den Berg/Anke van Reenen (2009): Morphological Atlas of the Dutch Dialects Volume II. Amsterdam: Amsterdam University Press. 180 Seiten. - Kürschner, Sebastian (2010)
UnivIS-Import:2015-03-09:Pub.2010.phil.dgeko.LGDSM.rezens_4
Keywords: Rezension; review; Morphologie; morphology; Dänemark; Dialekt; Dutch dialect

Schmidt-Wiegand, Ruth (b. 1926) - Kürschner, Sebastian (2006)
UnivIS-Import:2015-04-20:Pub.2006.phil.dgeko.LGDSM.schmid
Keywords: Lexikon; Ruth Schmidt-Wiegand

Semantische Konditionierung in der Pluralallomorphie deutscher Dialekte - Kürschner, Sebastian (Dialektale Morphologie, dialektale Syntax. Beiträge zum 2. Kongress der Internationalen Gesellschaft für Dialektologie des Deutschen, Wien, 20.-23. September 2006, 2008)
UnivIS-Import:2015-04-16:Pub.2008.phil.dgeko.LGDSM.semant
Keywords: Deutsch; Dialekt; Pluralallomorphie

Sprachliche Variation im Bairischen von São Bento do Sul, Brasilien - Habermann, Mechthild; Kürschner, Sebastian (Struktur von Variation zwischen Individuum und Gesellschaft. Akten der 14. Bayerisch-Österreichischen Dialektologietagung, Salzburg, 2022)

Strategies in the recognition of Dutch words by Germans - Kürschner, Sebastian (Phonetics in Europe. Perception and production, 2013)
Keywords: Niederländisch; Deutsch; Verstehbarkeitsforschung

The interaction of gender and declension in Germanic languages - Kürschner, Sebastian; Nübling, Damaris (Folia Linguistica, 2011)
In the Germanic languages, gender and declension are two classification systems with a restricted functional load. Still, both persist in many languages, and in  some of these languages they are even intimately interrelated, i.e. gender can be  predicted based on declension, or declension can be predicted based on gender. Several Germanic languages and dialectal varieties of German are compared with respect to this link between gender and declension. Based on contrastive data, the interaction seems to depend on the level of complexity, i.e. the number of declensions and genders. When complexity decreases, the conditioning of both categorization systems is either more strongly interrelated (leading to parallelization in the most extreme cases), or gender and declension are dissociated and bound to new, more transparent conditioning factors. The developments are interpreted against the background of the hypothesis that gender and declension are used complementarily in profiling the number category: gender profiles the singular, whereas declension profiles the plural.
Keywords: declension; gender; Germanic languages; German; inflectional morphology

The reflection of historical language contact in present-day Dutch and Swedish - Gooskens, Charlotte; van Bezooijen, Renée; Kürschner, Sebastian (Language contact; new perspectives, 2010)
In the present study we quantitatively examined similarly constructed samples of formal spoken Swedish and Dutch in order to compare the composition of the lexicons. Results showed that Swedish has many more loans than Dutch, namely 44.4% against 27.9%. Within the Swedish loans there is a large compartment of Low German (38.7%), whereas most loans in Dutch have a French origin (63.8%). The differences in terms of the number and distribution of loanwords between the lexical profiles of Swedish and Dutch appear to be stable, as they were attested both in the present study and in previous studies. They can be attributed to differences in the linguistic distances between source and borrowing languages and to differences in the intensity of the contacts.
Keywords: language contact; Dutch; Swedish; loanwords

Verfugung-s-nutzung kontrastiv. Zur Funktion der Fugenelemente im Deutschen und Dänischen - Kürschner, Sebastian (Tijdschrift voor Skandinavistiek, 2005)
UnivIS-Import:2015-03-09:Pub.2005.phil.dgeko.LGDSM.verfug
Keywords: Fugenelemente; Deutsch; Dänisch

Verstehen nah verwandter Varietäten über Staatsgrenzen hinweg [Understanding closely relates varieties across national borders] - Kürschner, Sebastian; Gooskens, Charlotte (Dynamik des Dialekts - Wandel und Variation. Akten des 3. Kongresses der Internationalen Gesellschaft für Dialektologie des Deutschen (IGDD), 2011)
UnivIS-Import:2015-04-16:Pub.2011.phil.dgeko.LGDSM.verste
Keywords: Verstehbarkeit; Varietäten

Von flacher Flagge und matter Macht: Verstehen niederländischer und schwedischer Kognaten durch Deutschsprachige - Kürschner, Sebastian (Sprache im Gebrauch: räumlich, zeitlich, interaktional. Festschrift für Peter Auer, 2014)
Keywords: Deutsch; Schwedisch; Niederländisch; Kognat; Verstehbarkeitsforschung

Von Hans Christian Andersen zu HC And - Formen der Nutzung und Nutzbarmachung des Dichternamens im Dänischen [On the usage of Hans Christian Andersen's name in Danish] - Birkmann, Thomas; Kürschner, Sebastian (Hans Christian Andersen zum 200. Geburtstag: "Mein Leben ist ein schönes Märchen, so reich und glücklich.", 2005)
UnivIS-Import:2015-04-20:Pub.2005.phil.dgeko.LGDSM.vonhan

Von Volk-s-musik und Sport-Ø-geist im Lemming-Ø-land. Af folk-e-musik og sport-s-ånd i lemming-e-landet: Fugenelemente im Deutschen und Dänischen. Eine kontrastive Studie zu einem Grenzfall der Morphologie. - Kürschner, Sebastian (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2003)
Die Arbeit behandelt kontrastiv System und Funktion der Fugenelemente in Nominalkomposita im Deutschen und im Dänischen. Fugenelemente sind Einheiten, die fonisch in der Wortfuge von Komposita auftreten können (z. B. Volk-s-musik), aber auch als Nullrealisierung vorzufinden sind (z. B. Sportsgeist). Aufgrund ihrer formalen Ähnlichkeit zu Flexiven wird ihre Distribution und Funktion häufig mit der Flexionsmorphologie in Verbindung gebracht. Es zeigt sich jedoch schon an Beispielen wie Verfassung-s-schutz, dass die formale Ähnlichkeit keine Bedeutungsübereinstimmung oder Distributionsparallelen zu Flexionssuffixen zur Folge haben muss: Das feminine Erstglied Verfassung kann kein Genitiv-s tragen (vgl. Gen. Sg.: der Verfassung). Das System der Fugenelemente lässt sich vielmehr an linguistischen Eigenschaften des Erstglieds festmachen, die sich sowohl auf fonetisch-fonologischem (Auslaut, Wortakzent, Silbenzahl), morphologischem (Derivationssuffixe, morphologische Komplexität, Flexionsklasse), etymologischem (Entlehnung) und semantischem Niveau bewegen können (semantische Merkmale). Zur Identifizierung von Distributionskriterien für Fugenelemente wurden Komposita in einem großen Korpus in mehreren Schritten analysiert. Dazu wurden Reihen identifizert, die auf die produktive Distribution der Fugenelemente aufgrund linguistischer Kriterien hinweisen können. Diese wurden anhand eines Produktivitätstests verifiziert. Das Ergebnis zeigt für beide Sprachen eine große Systematisierbarkeit auf, die nur durch das Bestehen idiosynkratischer Bildungen durchbrochen wird. So können neben der produktiven Distribution der Fugenelemente lexikalisierte Verbindungen weiter bestehen. Nach einer Einleitung (Kap. I) wird das Thema zunächst theoretisch bearbeitet (Kap. II). Einer Definition von für die Arbeit zentralen Begriffen folgt eine kontrastive Einführung in Fonologie und Flexionsmorphologie der betrachteten Sprachen. Ein Forschungsüberblickt führt anschließend zur sprachgeschichtlichen Entstehung und Entwicklung der Fugenelemente aus Flexionssuffixen über. Anschließend werden Theorien zur Systematisierung der Einheiten und zu ihrer Funktion dargestellt. Die im Kapitel II eingeführten theoretischen Konzepte werden in Kapitel III anhand einer Korpusanalyse überprüft. Systematisch werden die verwendeten Korpora und die entwickelte Methode vorgestellt. Die einzelsprachlichen Analysen zum Deutschen und Dänischen werden anschließend mit einer großen Zahl von Beispielen dargestellt. Aufgrund der einzelsprachliche Ergebnisse wird eine Kontrastierung der beiden Sprachen in Bezug auf ihr Fugensystem vorgenommen und durch weitere Analysen vertieft. Das Ergebnis zeigt in großen Teilen Ähnlichkeiten der Distribution auf. Fugenelemente treten im Deutschen wie im Dänischen an Erstgliedern mit einer Menge von Derivationssuffixen auf, die Nullfuge erscheint regelmäßig an nicht ins System integrierten Fremdwörtern. Übereinstimmung findet sich auch in bestimmten fonologischen Kriterien. Neben den Parallelen zeigen sich aber auch deutliche Divergenzen im deutschen und dänischen System: Semantische Kriterien zeigen sich primär nur im Dänischen, gleichzeitig spielen hier die flexionsmorphologische Kriterien wie die Deklinationsklasse im Gegensatz zum Deutschen keine Rolle. Zum Abschluss der Analyse werden Erkenntnisse zu System und Funktion der Fugenelemente und zur Lexikontheorie formuliert. Fugenelemente scheinen in beiden Sprachen eine ähnliche Funktionalisierung als Gliederungsmarker zu durchlaufen, die sich am deutlichsten am gehäuften Auftreten der -s-Fuge nach morphologisch komplexen Erstgliedern zeigt. Dabei scheint der Funktionalisierungsprozess im Dänischen schon weiter fortgeschritten zu sein als im Deutschen. Die Ergebnisse werden in Kapitel IV in einem Schlusswort zusammengefasst. Der umfangreiche Anhang umfasst das vollständige verwendete Material sowie Kommentare zu methodischen Problematiken.
UnivIS-Import:2015-04-02:Pub.2003.phil.dgeko.LGDSM.vonvol
Keywords: Fugenelement; Deutsch; Dänisch; Morphologie

Wat weet de Nederlander van de herkomst van Nederlandse woorden? [Was wissen Niederländer über die Herkunft niederländischer Wörter? What do Dutch speakers know about the etymology of Dutch words?] - van Bezooijen, Renée; Gooskens, Charlotte; Kürschner, Sebastian (Tijdschrift voor Nederlandse Taal- en Letterkunde, 2009)
There have been quite a few studies exploring popular ideas and knowledge of variation in the Dutch language area. However, emphasis has always been on the geographic dimension, historic variation remaining underexposed. In the present article we present the results of an investigation which focussed on the knowledge that non-linguists possess of the origin of high-frequent words in present-day spoken Dutch. We hypothesized that loans of English origin would be better recognized than loans from other languages because they are more recent and have been less adapted to the Dutch language. This hypothesis was confirmed. Although words of English origin constitute a relatively small portion of the high-frequent part of the lexicon of present-day spoken Dutch, they are far better recognized than words of German, French and Latin origin.
Keywords: Dutch; ethymology

Wortschöpfung am Beispiel der Personenspitznamen: Von "Fi", "Pipo" und "Ankaninchen" - Kürschner, Sebastian (Worte über Wörter. Festschrift für Elke Ronneberger-Sibold, 2015)
Keywords: Wortschöpfung; Namensforschung

Yngling-e-land-s-hold-s-mål-manden og hans hold-kammerater er land-s-mænd. Om fugeelementer i sammensatte ord [On linking elements in Danish compounds] - Kürschner, Sebastian (Mål og mæle, 2005)
UnivIS-Import:2015-03-09:Pub.2005.phil.dgeko.LGDSM.ynglin
Keywords: linking element; Danish